OC-022 Development And Outcome Of Intestinal Failure In Crohn's Disease: 3 Decades Of Experience From A National Referral Centre. (9th June 2014) - Nixon, E; Allan, P; Sidhu, S; Abraham, A; Teubner, A; Carlson, G; Lal, S
Abstract : Introduction: Intestinal Failure (IF) is a rare complication of Crohn's disease (CD) which carries significant morbidity, for which there is a relative paucity of data. We describe a large series of patients with CD and IF and evaluate factors associated with IF development. Methods: This was a retrospective study from a prospectively maintained database of patients referred to a national IF centre. Patients with CD were identified if on home parenteral nutrition (PN) for at least 12 months in the period between 1980–2011, and case notes were reviewed. Severe IF was defined as onset of IF within 15 years of CD diagnosis. Comparison of frequencies was performed using the Chi-squared test. Multivariate logistic regression models were used to identify independent associated factors after univariate analysis. Results: 78 patients were identified. The median time from CD diagnosis to commencing PN was 120 (12–552) months. Median time from CD diagnosis to first surgery was 36 (0–312) months. Patients underwent a median of 3 (1–7) small bowel (SB) resections prior to commencing PN, and the median remnant SB length was 130 (40–375) cm. Patients underwent a total of 312 operations but data were unavailable for 3 of these. The primary indication for the first surgery was stricturing (61.5%), followed by penetrating (23.1%) and inflammatory (15.4%) disease. Operative complications were higher in patients undergoing emergency (37/85; 43.5%) vs. elective (53/224; 23.7%) procedures (p = 0.001) and in surgeries performed outside (87/255; 34.1%) vs. within (3/54; 5.6%) the IFU (p < 0.0001)). 234 subsequent operations were undertaken after the first, but indication data were missing in 7 operations; operative complications were the primary indication for surgical intervention in (76/227) 33.5% of cases after the first surgery. In multivariate analysis, severe IF was associated with surgical complications (p = 0.003), higher number of SB resections (p = 0.005) and earlier age of CD diagnosis (p = 0.005). 25/78 (32.1%) patients achieved nutritional autonomy during a median follow-up of 36 (12–376) months after commencing PN. There were 68 documented catheter infections (0.42 infections/1000 catheter days) in this patient cohort. 9 patients died during follow-up as a result of liver disease (n = 3), complex CD/overwhelming sepsis (n = 2) or other causes (n = 4). Conclusion: Recurrent surgeries with operative complications are significant factors leading to severe IF. These are important considerations in guiding therapeutic decisions in CD, given the morbidity associated with chronic IF. Disclosure of Interest: None Declared.